Agregado reciclado de construção e demolição: influência em propriedades de argamassas para revestimento - Oliveira, Maria Elane Dias de (2012)
Excessive consumption of natural resources in construction has contributed to greater environment degradation. An alternative to minimize this consumption is the production of aggregate arising from construction and demolition waste for the production of concrete and mortar. This study aimed to evaluate the influence of aggregate from CDW in the production of mortar coating. In this sense the natural aggregate was replaced by the recycled aggregate contents of 0%, 25%, 50% and 75% by weight. The mixtures were produced with dash 1:6 (cement:aggregate) and consistency index set at 295 ± 10mm. The influence of aggregate CDW was evaluated through properties in the fresh state (consistency, water retention and density) and hardened state (compressive strength, tensile strength in bending, tensile bond strength, drying shrinkage, absorption water immersion and wicking). Results showed the increase water retention by incorporating CDW to the mixture. In the hardened state, the mortar with aggregate CDW had better mechanical performance compared to the mortar with natural aggregate, the behavior is more significant for the mixture with 75% of CDW.